2015
DOI: 10.4278/ajhp.130228-quan-89
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Supervised Worksite Exercise Program on Back and Core Muscular Endurance in Firefighters

Abstract: A supervised worksite exercise program was safe and effective in improving back and core muscular endurance in firefighters, which could protect against future low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 29 publications
3
53
0
1
Order By: Relevance
“…Our findings are consistent with the literature [9,34,35]. The novel finding of our study is that changing the training surface and reducing visual feedback in trunk stabilization exercises could be effective on improving dynamic balance, which aligned with previous studies [34][35][36]. The improvement in dynamic balance after 6-week CSTP could be explained in the following reasons.…”
Section: Dynamic Balance Performancesupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with the literature [9,34,35]. The novel finding of our study is that changing the training surface and reducing visual feedback in trunk stabilization exercises could be effective on improving dynamic balance, which aligned with previous studies [34][35][36]. The improvement in dynamic balance after 6-week CSTP could be explained in the following reasons.…”
Section: Dynamic Balance Performancesupporting
confidence: 92%
“…The potential benefit of Swiss ball and balance pad may be due to the increased muscle activation on unstable training surface [9,25], which explain the positive changes in SBFPKT. Indeed, it has already been demonstrated that exercises involved switching the base of support and unexpected turbulence would improve muscle maximal voluntary contraction [36]. The involvement of Swiss ball and balance pad in our 6-week CSTP was likely to produce positive effect not only in dynamic balance but also trunk endurance including back-extensor endurance.…”
Section: Effectiveness Of Swiss Ball and Balance Padmentioning
confidence: 78%
“…Through introduction to educational content, firefighters may change their workplace practices, thereby reducing their risk for injuries. For instance, Mayer et al (2015) assessed the impact of an on-duty back and core muscular endurance exercise program for firefighters; after 24 weeks, the exercise group exhibited 12% greater back muscle endurance ( p = .02) and 21% greater core muscle endurance ( p < .001). The cost savings in terms of reduction in days lost to injury can be significant.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that the working population often suffers from poor muscular fitness and musculoskeletal pain, affecting the backbone, neck, shoulders, and hips [17,18]. Symptoms such as low back pain have been rather prevalent due to sedentary lifestyles, and prolonged-time workers spent sitting at their offices [19]. With this in mind, exercise that improves muscular fitness and joint flexibility may positively affect work performance and decrease musculoskeletal pain in this population.…”
Section: Non-traditional Pa Programs At Workplacementioning
confidence: 99%